Предмет: Алгебра, автор: Mimish12

ДАЮ 100 БАЛЛОВ!!
1) Упростить.
a) (4b-x)+(146-6126
а) (x+)34x3
в) (2+4)2*(a-2)(a+2)
г) (a-36)+(30+6)
д) a2+ (за-вре e) 96² - (9.-36/² ж) (a-3P-(2-0) а-з 2​

Приложения:

Ответы

Автор ответа: NNNLLL54
1

Ответ:

Упростить выражения . Применяем формулы сокращённого умножения .

\bf 1)\ \ (4b-7)^2+(14b-6)^2-6b=\\\\=16b^2-56b+49+196b^2-168b+36-6b=212b^2-230b+85\\\\2)\ \ (x+1)^3+x^3=x^3+3x^2+3x+1+x^3=2x^3+3x^2+3x+1\\\\3)\ \ (a+4)^2-(a-2)(a+2)=(a+4)^2-(a-4)=a^2+8a+16-a+4=\\\\=a^2+7a+20\\\\4)\ \ (a-3b)^2+(a+3b)^2=(a^2-6ab+9b^2)+(a^2+6ab+9b^2)=2a^2+18b^2\\\\5)\ \ a^2+(3a-b)^2=a^2+9a^2-6ab+b^2=10a^2-6ab+b^2

\bf 6)\ \ 9b^2-(a-3b)^2=9b^2-(a^2-6ab+9b^2)=-a^2-6ab\\\\7)\ \ (a-3)^2-(2-a)^2=a^2-6a+9-(4-4a+a^2)=5-2a  

Похожие вопросы